2019
DOI: 10.3390/ijms21010031
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Fiber Composition during Gestation Induces Changes in Offspring Antioxidative Capacity, Inflammatory Response, and Gut Microbiota in a Sow Model

Abstract: To study the effects of maternal dietary fiber composition during gestation on offspring antioxidant capacity, inflammation, and gut microbiota composition, we randomly assigned 64 gilts to four treatments and administered diets with an insoluble/soluble fiber ratio of 3.89 (R1), 5.59 (R2), 9.12 (R3), and 12.81 (R4). Sow samples (blood and feces at gestation 110) and neonatal samples (blood, liver, and colonic contents) were collected. The results showed that sows and piglets in R1 and R2 had higher antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 73 publications
2
55
0
Order By: Relevance
“…Intestinal microbiota with high diversity could be more stable and healthier than low diversity, while low diversity is always associated with metabolic syndrome and inflammation [ 27 , 28 ]. At phylum level, Proteobacteria , Firmicutes , Bacteroidetes , and Actinobacteria were the most predominant phyla in the colon of newborn piglets, which were consistent with those previously found in the colon of newborn piglets [ 16 ]. Maternal high fiber intake significantly increased the abundance of Acidobacteria and showed a tendency to increase the abundance of Bacteroidetes .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Intestinal microbiota with high diversity could be more stable and healthier than low diversity, while low diversity is always associated with metabolic syndrome and inflammation [ 27 , 28 ]. At phylum level, Proteobacteria , Firmicutes , Bacteroidetes , and Actinobacteria were the most predominant phyla in the colon of newborn piglets, which were consistent with those previously found in the colon of newborn piglets [ 16 ]. Maternal high fiber intake significantly increased the abundance of Acidobacteria and showed a tendency to increase the abundance of Bacteroidetes .…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, it has also been reported that maternal high fiber intake increased plasma SCFAs levels of maternal and offspring mice and regulated T cell differentiation in offspring mice [ 14 ]. Our study showed maternal fiber intake improved testis cell development and altered testicular proteome of offspring piglets [ 15 ]; we also found the composition of dietary fiber in pregnancy diet affect the intestinal microbiota composition of offspring piglets [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that dietary exogenous CAT decreased H 2 O 2 and MDA concentrations in the jejunal mucosa of piglets. H 2 O 2 is one of the major ROSs in the body, and MDA, a secondary product of lipid oxidation, has been widely considered to be an index by which to monitor the degree of lipid peroxidation [29]. Both H 2 O 2 and MDA are closely associated with cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…The short-chain fatty acids (SCFAs) in piglet colonic digesta were measured according to the protocol from a previous study [29]. Briefly, 0.7 g of colonic digesta samples were suspended in 1.5 mL of distilled water and allowed to stand for 30 min, followed by being centrifuged for 15 min at 15,000× g at 4 • C. Then 1 mL supernatant was transferred and mixed with metaphosphoric acid (0.2 mL, 25%, w/v) and crotonic acid (23.3 µL, 210 mmol/L).…”
Section: Short-chain Fatty Acids Concentration Analysismentioning
confidence: 99%
“…Short-chain fatty acids involved in the regulation of sow metabolism, immunity, and cell proliferation ( Li et al., 2019 ; Wu et al., 2020 ; Xu et al., 2020a ). Dietary supplementation of 3% purified fiber-mixture significantly increase the concentrations of butyrate and propionate in the feces of sows, which was related to the increase in the abundance of Eubacterium-hallii-group and Bacteroides in the gut ( Wu et al., 2020 ).…”
Section: Biological Effects Of Dietary Fiber Fermentation By-productsmentioning
confidence: 99%